Uses (and Abuses) of Ore Deposit Models in Mineral Exploration - Hogson, C. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1990)
Abstract An ore deposit model is a conceptual and/orempirical standard, embodying both the descriptive features of the deposit type, and an explanation of these features in terms of geological processes. The descriptive features of models serve as criteria for exploration area selection ("area selection criteria").How they are used in this function dependson the scale of their spatial association withore, on our confidence that they are reliable indicators of ore, and on the extent to which they are prefer entially associated with economically better deposits. The geological, geochemical, and geophysical techniques used in exploration, and exploration strategy depend on area selection criteria. The relative importance of area selection criteria can be determined from their relative frequency of association with ore in a representative sample of the deposit population, resulting in an empirical model. A genetic model is derived by considering the genetic relationship of area selection criteria to ore. The weak links in model building are the lack of effort which goes into systematically assembling the data on the known population of deposits, and the weak scientific under pinnings of the genetic interpretation. Both of these factors influence exploration by leading to inappropriate assessments of the relative importance of area selection criteria. In addition,there are a number of human foibles which commonly lead to shortcomings in the development and use of models. The most significant of these is our tendency to rely toomuch on too simple models. We do this to avoid the discomfort of uncertainty and confusion which inevitably comes when we are called on to assess exploration situations.The history of exploration for massive base-metal sulphide deposits and gold deposits in the Canadian Shield provides a good illustration of the influence of models on area selection criteria, and thereby, on exploration strategy and techniques.